Effects of Recycled Jute Fibre Inclusion on Strength Properties of Soil - Gupta, Gopesh (My University, 2019)
The biggest challenge in developing country like India is to build a full network of road system limited financial source available. With the evolution of highway and growing traffic on roads, new materials and construction technique are required to provide civil engineers with alternative to traditional road construction practices. For Geotechnical and highway engineer’s improvement in subgrade has always been an area of concern. Use of locally available material can considerably lower down the construction cost. Now-a-days several waste by-products and material have been used to enhance the properties of soil. Example fly ash, waste plastic products, coir etc. The research has been done in this area to improve the engineering properties of locally available soil by adding randomly distributed recycled jute fibre. In this study, jute fibres were randomly mixed with the soil, then a series of CBR test and Direct Shear test were conducted to evaluate the strength and shear parameters of the subgrade soil. In this study, the length of fibre taken was 0.5inch, 1.0inch, 1.5inch and 2.0inch. The percentage of jute fibre by dry weight of soil was taken as 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% and 4.0%. Result from CBR test and Direct Shear test established that the addition of jute fibre in subgrade soil give efficient strength and stability to subgrade. From CBR test it was concluded that CBR value increases with increase in fibre content upto certain percentage but with further addition of jute fibre iv the value of CBR decreases. The same trend is found out for the direct shear test. The permeability test was also done on the parent soil and the soil blended with jute fibre. The pavement section has been designed with the help of IIT-PAVE software. The pavement section has been designed for both normal subgrade and the modified subgrade using randomly distributed jute fibre. The critical strain value at the top of subgrade and at the bottom of the bituminous layer has been analysed and compared with the allowable values as per IRC: 37-2018 for the traffic loading of 30 msa, 50 msa and 100 msa for the for the four-lane state highway project. The reduction in thickness and saving in project cost has been compared for different subgrade with the different size of jute fibre and by varying content of jute fibre.
Keywords: Jute Fibres; IRC 37; CBR